The Future of Gene Therapy: Revolutionizing Modern Medicine - Akram, Muhammad; Khan, Alam Afroz Urooj; Umaru, Isaac John (Darul Yasin Al Sys, 2025)
The use of gene therapy paired with advanced technology may one day enable chronic illnesses, cancerous diseases, and even genetic defects to be treated via DNA alterations. With developments and promising results in gene CRISPR-Cas9 editing technology, improved treatments and promising results from clinical trials have made gene therapy a possibility. It is also predicted that gene therapy will be used in the future to combat heart issues, cancer, neurological diseases, and other hereditary attributes. Nonetheless, metastatic issues pertaining to ethics, engagement, spending, and the probability of negative consequences over time still remain. In the case of augmented medicine, incorporating stem cells with new artificial intelligence technology will ensure better and more accurate treatment along with greater personalization of gene therapies. This is expected to lead to a whole new realm of precision medicine.